PENGARUH LIKUIDITAS, CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA ( BEI) PERIODE TAHUN 2016-2020 - Safitri, Winda; Efni, Yulia; Fitri, Fitri (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to determine the effect of liquidity, corporate social responsibility and institutional ownership on profitability. This research was conducted on companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in the 2016-2020 period. The population in this study amounted to 80 companies, while the sample in this study amounted to 28 companies using a purposive sampling method. Data analysis using multiple linear regression. Partially, liquidity has an insignificant negative effect on profitability, while corporate social responsibility has a non-significant positive effect on profitability, and institutional ownership has a significant positive effect on profitability in companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2016-2020.